The battles of the prophet - Ahmad Zidan (Pustaka Al-Shafa, 2010)
[This book] comprises a great length of historical moments which most of them brought a light to the development of legal verdict and sanction. It covers every aspects of Muslim struggle in battlefields which proves to mankind that Islam is not a religion of 'sword', but it rather stands firmly as a defence and shelter for the entire Ummah particularly the oppressed and the tyrannized.